STRUKTUR MIKRO DAN SIFAT MEKANIS ALUMINIUM PADUAN SERI 6063 HASIL COR DARI CETAKAN LOGAM, PASIR RESIN FURAN DAN PASIR KOMOSSA - Chris Marvin; Eddy S Siradj; Sobron Yamin Lubis (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Material developments in Indonesia is already very advanced rapidly certainly need high level of violence but has a mass of light. Aluminum should be developed because it possesses a lightweight and available in the land of our country that is rich in agricultural products. As an alternative to strengthen aluminum alloy that is with Si and Mg, as well as the rapid cooling process when smelting. This study was conducted to observe the microstructure and mechanical properties of the raw material of aluminum alloy series 6063. Tests conducted with metal mold, furan resin sand mold, commossa sand mold, the cooling rate of each mold will affect the hardness of the material which can be seen microstructure with microstructural observations. The survey results revealed that the aluminum with a metal mold casting has a hardness of 54 HRB, furan resin sand has a hardness of 40 HRB, sand commossa has a hardness of 33 HRB. Metal mold has a shock force of 0,316 J/mm2, particularly a furan resin sand shock force of 0,265 J/mm2, commossa sand has a shock force of 0.206 J/mm2. Metal mold has a high hardness compared with furan resin sand rated second, while the sand was rated commossa end but increasingly harsh mean tenacity of a material value will increase. According to the test micro structure, the aluminum is brittle, the distance or the distribution of grain will be a meeting or a lot.